2007
DOI: 10.1080/00365520600930826
|View full text |Cite
|
Sign up to set email alerts
|

A simple clinical score predicts high risk for upper gastrointestinal hemorrhages from varices in patients with chronic liver disease

Abstract: A simple clinical score can predict the risk for upper GI bleedings in patients with chronic liver disease. This Bleeding Risk Score may help to supplement current endoscopic and clinical approaches to identify high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
0
22
0
3
Order By: Relevance
“…Nine of 13 patients in this study had surgery for gastric varices. Bleeding from gastric varices is still diffi cult to control and has a high mortality rate, 21 whereas bleeding from esophageal varices can be controlled in more than 98% of patients using endoscopic treatment. 22 Primary bleeding from gastric varices is uncommon, occurring in 2%-5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nine of 13 patients in this study had surgery for gastric varices. Bleeding from gastric varices is still diffi cult to control and has a high mortality rate, 21 whereas bleeding from esophageal varices can be controlled in more than 98% of patients using endoscopic treatment. 22 Primary bleeding from gastric varices is uncommon, occurring in 2%-5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Liver cirrhosis, a malignant liver disease which is followed by liver failure resulting in high mortality, is also frequently associated with gastrointestinal (GI) complications such as GI bleeding and malnutrition [3,34,43]. Our previous studies showed that increased diversity of virulence factors and instability of the gut microecosystem are related to the severity of liver injury [27].…”
Section: Introductionmentioning
confidence: 97%
“…Portal hypertension was established according to the following criteria: Portal vein diameter > 12 mm and/or presence of esophageal varices and/or splenomegaly. Alterations in the Quick index were established when the international normalized ratio (INR) was higher than 1.2 [33] . The ICG test was performed by pulsidensitometry (Limon PC5000, Pusion Medical Systems, Munich RFA).…”
Section: Methodsmentioning
confidence: 99%